For this problem, you first plug y=3x-14 in to x+3y=4
The equation will thin look like this: x+3(3x-14)-14
since the value of y is equal to 3x-14, that means that 3y=3(3x-14)
then you distribute 3 into 3x-14 it will look like this: 3*(3x)+3*(-14) (9x)+(-42) 9x-42
now you should have written x+9x-42=14
next, combine like terms x+9x-42=14
10x-42=14 <u>+42 +42</u> 10x=56
now, you divide 56 by 10 <u>10x</u>=<u>56</u> 10 10
x=5.6
okay, now that x has been solved for, we now need to find the value of y the simplest way to go about this is to choose the equation that already has y by its-self. y=3x-14 plug 5.6 in to x y=3(5.6)-14 now solve for y
y=(16.8)-14 y=2.8
FINAL ANSWER y=2.8 x=5.6
if you want to check your work, you can plug x and y into either equation